The Role of Digital Technologies in Distance Learning - O. A. Gironkina; N. A. Medvedeva; E. E. Sokolova (Открытое образование (Москва))
Purpose. This article is devoted to the analysis of the issues of using digital technologies in foreign language classes in higher educational institutions. The relevance of the paper is explained by the fact that the issue of digitalization of the educational environment attracts the attention of researchers. Therefore, in 2019, the federal project “Digital Educational Environment” was developed, which proposed a plan of measures until 2024 aimed at “creating and implementing a digital educational environment in educational organizations, as well as ensuring the implementation of the digital transformation of the education system”.Materials and methods. New technologies require new approaches to learning, reworking of learning content and development of new principles. Despite the abundance of scientific papers written on this issue, the authors of the article contribute by making a critical review of the existing literature, as well as describing their experience of teaching a foreign language in the era of digitalization, answering the following research questions:1. What digital learning tools are best used in foreign language classes at a university?2. How can a teacher communicate with students in a digital network?3. How to carry out quality control and assessment of knowledge? Research results. The issues stated and solved by the authors are the problems of academic deceit, loss of concentration, adequate assessment of students’ work on digital platforms. Online classes cause difficulties of both organizational and methodological nature. The most common challenges faced by teachers are reduced student involvement in the learning process, increased temptation to academic cheating, and the difficulty of organizing pair and group work. The article provides a thorough analysis of the most popular digital learning tools, identifying their advantages and disadvantages. Also, an algorithm is proposed aimed at solving the main difficulties: methods for increasing students’ interest when working with digital technologies are described, the speech value of educational material is considered, methods for updating typical tasks, correcting each other, responding, and holding attention. This analysis was carried out on the basis of the principles formulated by E. Passov, namely: the speech value of the material, individualization of tasks and novelty. The above solutions allow the teacher to diversify the activities in the classroom and increase the motivation of students without the involvement of special additional means of education.Conclusion. The article also proposes additional platforms and applications that allow you to diversify the types of activities in the classroom and conduct knowledge control. A separate section of the article is devoted to the control of students’ knowledge in the digital environment. Recommendations are presented on how to use additional resources and applications that allow you to create tests and interactive tasks, as well as ways to exercise control without using additional applications.